Semi-empirical calculation of 12CH3D-H2 broadening coefficients and their temperature-dependence exponents for rovibrational lines in parallel bands. (May 2019) - Dudaryonok, A.S.; Lavrentieva, N.N.; Buldyreva, J.
Highlights: Calculations of CH3 D-H2 line widths for large ranges of quantum numbers. Theoretical evaluation of temperature-dependence exponents for line widths. Line-lists of collisional broadening parameters in R-P-Q-branches of parallel bands. Abstract: Hydrogen-broadening coefficients and their temperature-dependence exponents for 12 CH3 D ( J,   K ) lines in the parallel (Δ K  = 0) ν3 band are computed by a semi-empirical method employing analytical Anderson-type expressions with a few-parameter correction factor introduced to account for various deviations from Anderson's theory approximations. On the basis of experimentally observed J -dependences of line widths, this correction factor is taken in the traditional two-parameter form, and the parameters are determined from fits on some room-temperature measurements. After validation by comparison with available experimental data, the calculations are done for extended ranges of rotational quantum numbers (0 ≤  J  ≤ 70, 0 ≤  K  ≤ 20) typically requested for spectroscopic databases. To get the temperature-dependence exponents, computations with the room-temperature parameters' values are repeated for various temperatures in the room-temperature containing range 200–400 K recommended for HITRAN and least-squares fit procedures are applied. Detailed P-Q-R-line lists are provided. With negligible vibrational dependence of CH3 D line widths, these data can be also employed for other A1 -type bands.